Transformative Da'wah in Indonesia: Challenges of Equity and Opportunities for Synergy of Islamic Organizations and States - Saraka, Muh. Yahya; Monarshi, Evri Rizqi; Shabrina, Nadya (Fakultas Dakwah UIN Saizu Purwokerto, 2025)
This research critiques the conventional understanding of da'wah, often limited to propagation (tabligh), while overlooking other vital dimensions such as guidance (irsyad), administration (tadbir), and empowerment or consolidation (tathwir/tamkin). The study examines the development of transformative da'wah in Islamic institutionalization, education, and economic progress within Indonesia’s nation-building process. The research adopts a social conflict perspective using a qualitative descriptive approach with a literature review and Max Weber's social change theory. Findings indicate that government focus remains centred mainly on da'wah as tabligh. However, transformative da'wah, particularly through Islamic educational institutions, requires a roader commitment to ensure equitable access across the nation. In the economic realm, establishing Islamic banks reflects significant progress in transformative da'wah. However, further improvement is needed in educational funding allocation. In the microeconomic context, Baitul Mal Wa Tamwil (BMT) faces regulatory overlaps that necessitate clearer policy support. The research concludes that while transformative da'wah in education and economy is moving positively, sustained government commitment is critical to optimize its role in strengthening Islamic values and contributing meaningfully to national development.